Pendidikan Karakter MI Al-Ma’arif Merauke: Analisis Kontribusi Tri Pusat Pendidikan - Ihsan Hamidi; Ahmad Fadlur Rahman Bayuny (Jurnal Ilmu Pendidikan dan Sains Islam Interdisipliner, 2023)
This study aims to explore and determine the extent of the role of the three education centers at MI Al-Ma'arif Merauke in building the character of students. The method used in this research is descriptive qualitative, namely a study that seeks to describe the phenomenon of a condition as it is through observation and direct interviews with informants and other sources that support the data collection of this research. The results of this study indicate that the three education centers at MI Al-Ma'arif Merauke are included in the good category, although there are still a number of things that need to be re-optimized so that the education and character building of students is maximized. The level of parental education greatly influences the education of children in the family. Good family education is determined by good human resources. The majority of the education community around MI Al-Ma'arif Merauke has a high school level education, not infrequently they even have a bachelor's degree. This greatly affects the education of children in the family and the education of children in society